Ideological Influences on Bilingual Coffee Shop Signs in Najran City: A Translation Perspective - Abduljalil Nasr Hazaea; Wagdi Rashad Ali Bin-Hady (Jurnal Arbitrer, 2026)
In a global era, English has an expanding role affecting everyday life, including commercial signs. The translation of these signs on culturally driven commodities such as coffee is a significant area of study, revealing broader sociolinguistic dynamics and ideological perspectives. This study investigates the translation features observed on coffee shop signs, exploring how ideological choices shape translation practices and their implications for visual identity. Employing Gu and Almanna’s model for categorizing street signs and Venuti’s concepts of domestication and foreignization, we analyzed bilingual coffee shop signs scattered in Najran city, Saudi Arabia. The findings delineate four predominant features in the assignment of bilingualism: pure Arabic and pure English (PA&PE), pure Arabic and English transliteration (PA&ET), pure English and transliterated Arabic (PE&TA), and mixed features (MF). Over half of the signs utilized PE&TA reflecting a foreignization strategy to reinforce English in the Saudi context while marginalizing Arabic. One quarter of the signs achieved a balance between PA&PE, indicative of domesticating translation practices. Mixed features are also found in coffee shop signs (17%), blending direct translation, transliteration, and adaptation techniques. Surprisingly, only 7% of the signs were in PA&ET aiming to support Arabic language presence for foreign visitors. While omission was mainly associated with PE&TA and PA&PE, addition was manifested with MF and PA&ET. The study concludes with practical recommendations for bilingual sign translation, contributing insights to translation studies and offering guidance for translators, policymakers, and businesses operating in bilingual environments.